PENGARUH MEDIA PERMAINAN TRADISIONAL CONGKLAK TERHADAP KEMAMPUAN BERHITUNG SISWA KELAS II SD NEGERI 08 PINANG SEBATANG TIMUR - Gilberdh Saragih Sumbayak; Irmina Pinem; Juliana; Antonius Remigius Abi; Anton Sitepu; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the traditional congklak game on the math abilities of second-grade students in Mathematics at State Elementary School 08 Pinang Sebatang Timur in the 2024/2025 academic year. This study used a quantitative method with a pretest-posttest experimental design in one group, involving 25 students as a sample. Data collection was conducted through learning outcome tests and student participation questionnaires, which had been tested for validity and reliability. The pretest results showed an average value of student learning outcomes of 49.6 with a low category, while the posttest results increased to 80.6 with a high category. The Pearson correlation test produced a coefficient of 0.968 with a significance of 5%, which indicates a strong positive relationship between the application of traditional congklak game media and students' arithmetic abilities. Furthermore, the results of the hypothesis test using the t-test obtained a value of t count ≥ t table, namely 18.450 ≥ 1.1708, which means there is a significant influence between the use of traditional congklak game media on students' arithmetic abilities. Thus, the research hypothesis states that there is a significant influence of the traditional game of congklak on students' arithmetic skills.